دراسة الحوادث الوعائية الدماغية لدى مرضى الرجفان الأذيني - سعيد, هالة; بله, حسام; شاهين, زهية (Latakia University Journal -Medical Sciences Series, 2019)
Objective: We aimed to explore the characteristics and clinical outcomes in ischemic stroke patients with AF or without AF. Methods and patients : A total of 157patients (52 with AF,105 without AF)who were referred to Tishreen University Hospital. Demographic, clinical, CT brain or MRI,extracranial ultrasound ,ECG and Echocardiography were did. Results were statistically significant when p-value<5%. Results: The mean age was 70 years ,the biggest frequency of ischemic stroke associated with AF is in the age ≥ 75 years ,and (70%) female sex ,while patients without AF were male sex( 65%) and younger .The lesions in AF patients accumulated in the middle cerebral artery territory (70%) ,while patients without AF most of them were lacunar infarctions (74%). IN patients with AF) 17 cases ,32%) died ,while patients without AF (8 cases, 7.6%) died. AF relevant to risk to infarction in the MCA ten times (OR=9.8 ,P =0,001) . Conclusions :Ischemic stroke associated with AF is a major cause of long- term disability and mortality in the elderly ,and is more frequent in females sex ,and the most cases are in the territory of MCA. الهدف : تهدف الدراسة اكتشاف الخصائص والنتائج السريرية في مرضى النشبة الإقفارية مع رجفان أذيني او غير مترافقة برجفان . طرق الدراسة والمرضى : تضمنت الدراسة 157 مريضا (52 مريض مع AF,105مريض دون AF) الذين راجعوا مشفى تشرين بين عامي 2018-2019.الخصائص الديموغرافية (الجنس ,العمر) الأعراض السريرية ,الموجودات الشعاعية (الطبقي المحوري للدماغ ,الرنين المغناطيسي للدماغ ,ايكو دوبلر لشرايين العنق ,تخطيط قلب كهربائي ,ايكو قلبي) . تعتبر النتائج هامة احصائيا عندما p-value >5%. النتائج : متوسط العمر كان 70سنة ,المجموعة ذات الانتشار الأعلى للحوادث الوعائية الدماغية الناجمة عن AF كانت بالأعمار ≤75 سنة , و(%70) من الجنس الأنثوي ,بينما المرضى دون AF كانوا ذكور (65%) وأصغر عمرا. الآفات في مرضى AF اصابت الشريان المخي المتوسط (70%),بينما الاصابة في مرضى دون AF كانت احتشاءات فجوية (74%). حدثت الوفاة في (17حالة ,%32),بينما في المرضى دون AF (8حالات ,7.6%) حدثت الوفاة AF . يترافق بخطر اصابة القطاع MCA بعشرة اضعاف من غيابه OR=9.8, P=0,001)) . الاستنتاجات :النشبة الاقفارية الناجمة عن الرجفان الأذيني تعد سببا رئيسيا لعجز طويل الامد والوفيات في الأشخاص المتقدمين بالعمر, وهي أكثر تكرارا في الجنس المؤنث وتصيب القطاع MCA في معظم الحالات